2019
DOI: 10.1080/09638237.2019.1630727
|View full text |Cite
|
Sign up to set email alerts
|

Adverse event monitoring in mHealth for psychosis interventions provides an important opportunity for learning

Abstract: We would like this piece to be considered for publication as an editorial and have therefore not provided an abstract. We are of course happy to be advised otherwise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
(50 reference statements)
1
22
1
Order By: Relevance
“…The report of some increase in awareness of voices or increase in voice activity in response to prompts during the week of EMA monitoring is important to note. This is consistent with other reports that EMA prompts can sometimes increase paranoia, bring back memories or distressing experiences, or lead to rumination or worry about relapse (Ben-Zeev et al, 2016; Bradstreet et al, 2019). Of the participants in this study, only one reported a worsening of symptoms in response to EMA prompts, with others noting changes in awareness of or presence of their voices without regarding it problematic.…”
Section: Discussionsupporting
confidence: 93%
“…The report of some increase in awareness of voices or increase in voice activity in response to prompts during the week of EMA monitoring is important to note. This is consistent with other reports that EMA prompts can sometimes increase paranoia, bring back memories or distressing experiences, or lead to rumination or worry about relapse (Ben-Zeev et al, 2016; Bradstreet et al, 2019). Of the participants in this study, only one reported a worsening of symptoms in response to EMA prompts, with others noting changes in awareness of or presence of their voices without regarding it problematic.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed , a study of daily BD mood tracking using mobile phone technology was shown to increase depressive symptoms in the intervention group [5]. In addition, in digital health interventions for psychosis, qualitative studies and adverse event reports suggest that routine self-assessment of symptoms may increase rumination on negative experiences, generate fear of relapse when negative changes in mental health are observed, or trigger distressing memories of episodes of psychosis [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The purposive sampling strategy for approaching service user participants was developed from early-stage observations of the recruitment process. These early observations suggested that the following features might be relevant implementation factors: service user gender, service users inputting the same score every day (which would impact on the ability of the intervention to detect change), frequency of engagement with peer support workers, and whether a participant had experienced a relapse and an adverse event during intervention usage [61]. Therefore, we aimed to speak to participants who demonstrated a variety of the aforementioned characteristics to understand their experiences.…”
Section: Methodsmentioning
confidence: 99%